Hard carbon negative electrode material and preparation method thereof for lithium ion battery
By using hard carbon materials prepared by taro raw materials, the problem of insufficient energy density and kinetic performance of existing lithium-ion batteries is solved, and a lithium-ion battery negative electrode material with high specific capacity and fast kinetics is achieved.
Patent Information
- Application Number
- CN202411549054.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
The energy density of existing lithium-ion batteries is close to the upper theoretical limit and the kinetic response is slow, which cannot meet the demand of modern energy systems for high-energy-density lithium-ion batteries.
Taro as raw material, and after freeze-drying, high-temperature treatment under an inert atmosphere, a hard carbon material with rich porous structure was prepared for the negative electrode of lithium-ion batteries.
It improves the specific capacity and kinetic performance of lithium-ion batteries, enhances the high-current discharge capacity, and has stable material properties, achieving efficient and stable circulation and excellent rate performance.
Smart Images

Figure CN119390051A_ABST
Abstract
Description
(I) Technical field
[0001] The present invention belongs to the technical field of lithium ion battery negative electrode materials, and specifically relates to a lithium ion battery hard carbon negative electrode material and a preparation method thereof, a lithium ion battery negative electrode, a lithium ion battery and electrical equipment. (II) Background technology
[0002] Energy has always been an important resource for the sustainable development and survival of mankind, and has promoted the rapid progress of human civilization. At present, the excessive consumption of fossil fuels and traditional energy such as oil, coal, and natural gas has caused energy shortages and serious environmental pollution problems. Therefore, there is an urgent need to develop sustainable and clean new energy to solve these problems. With the advancement of new energy technologies, renewable energy sources such as hydropower, wind power, geothermal power, and solar energy are considered to be an effective way to solve the above problems. However, these renewable energy sources cannot be used directly, have the disadvantages of regionality and intermittency, and cannot meet people's requirements for on-demand use. Therefore, among various energy development strategies, the development of reliable electrochemical energy storage systems is an effective way to solve this problem.
[0003] Lithium-ion batteries have been widely used in human production and life due to their good stability, high discharge capacity, low self-discharge and other characteristics. Their most important feature is that they can convert electrical energy and chemical energy with extremely low loss. However, with the rapid development of various electronic products, people's requirements for lithium-ion batteries have become more and more stringent; therefore, the development of lithium-ion batteries with good cycle stability, high specific capacity and high safety performance has become the focus of research in recent years. In lithium-ion batteries, the basic properties of electrode materials have a great impact on the development of the entire battery. So far, graphite is the most successful commercial carbon negative electrode key material, but because of its low lithium insertion specific capacity and after 40 years of exploration, the energy density of traditional lithium-ion batteries with graphite as negative electrode material is very close to the upper limit of theoretical energy density, and there are defects such as slow reaction kinetics, which cannot meet the needs of modern energy systems for high-energy-density lithium-ion batteries. Therefore, it is imperative to design practical strategies to produce new carbon negative electrode materials with higher capacity and fast kinetics.
[0004] Compared with graphite, biomass-derived carbon materials have unique microstructures such as larger interlayer spacing, more defects, higher surface area and closed voids. Due to their special and adjustable properties, biomass-derived carbon materials usually exhibit complex Li-ion storage mechanisms, which are different from the simple (de)intercalation of ions in graphite. Therefore, if these parameters are properly adjusted and optimized, better battery performance can be obtained. In addition, biomass materials have the advantages of abundance, low cost, environmental protection, and renewable, and have potential low cost. Biomass is one of the abundant renewable energy sources on the earth and plays a valuable role in the development of sustainable biomass-derived carbon materials for high energy density lithium-ion battery anodes. However, due to the wide variety of biomass resources, complex preparation processes and unclear lithium storage mechanisms, its application and development are limited. From this point of view, how to use cheap and widely available basic raw materials and prepare biomass-derived carbon materials through simple and efficient methods is the most desired goal of scientific and technical personnel.
[0005] On the other hand, there are many methods for synthesizing biomass carbon source materials, such as pyrolysis, hydrothermal pyrolysis, chemical activation pyrolysis, template-assisted pyrolysis, heteroatom doping pyrolysis, microwave-assisted pyrolysis, etc. In this study, we used freeze-drying followed by pyrolysis to obtain the desired carbon materials in a high temperature, oxygen-free, inert gas protected environment.
[0006] Based on the above discussion, we selected taro paste as biomass and used freeze-drying and heating to carbonize it, providing a new hard carbon negative electrode material for lithium-ion batteries and its preparation method. The raw materials are cheap and easy to obtain. It effectively solves the problem of lithium dendrites and can greatly improve the electrochemical properties of metallic lithium. (III) Summary of the invention
[0007] The purpose of this application is to provide a hard carbon material and a preparation method thereof, a lithium ion battery negative electrode, a lithium ion battery and electrical equipment to solve the above problems.
[0008] To achieve the above objectives, this application adopts the following technical solutions:
[0009] A method for preparing a hard carbon material using taro as a raw material, comprising:
[0010] Step 1: Steam the taro skin and add appropriate amount of water to make fine taro paste;
[0011] Step 2: After freezing in a refrigerator for 2 hours to set the shape, transfer to a freeze dryer for freeze drying to obtain a pretreated biomass hard carbon material;
[0012] Step 3: subjecting the material described in step 2 to high temperature treatment in a protective atmosphere;
[0013] Step 4: After the high temperature treatment, the active material in the crucible is taken out and pickled to remove salt impurities;
[0014] Step 5: Place the product obtained in step 4 in a constant temperature drying oven for drying;
[0015] Step 6: ball-mill the active material obtained in step 5, and sieve to obtain a powder with a particle size of 400 mesh;
[0016] Preferably, the cold trap temperature of the freeze-drying treatment is -100°C, the vacuum degree is 15 Pa, and the time is 72 hours;
[0017] Preferably, the high temperature treatment temperature is 500°C, 750°C, 1000°C, and the heating rate is 15°C.
[0018] / min;
[0019] Preferably, the gas in the protective atmosphere includes one or more of nitrogen, argon, carbon dioxide, and hydrogen, and the gas flow rate is 50-200 mL / min;
[0020] Preferably, the acid solution used in the pickling is hydrochloric acid with a concentration of 1 mol / L;
[0021] Preferably, the drying temperature is 80°C and the drying time is 10 hours;
[0022] Preferably, the ball milling time is 12h;
[0023] The present application also provides a hard carbon material, which is prepared using the hard carbon material preparation method.
[0024] The present application also provides a lithium ion battery negative electrode, the raw materials of which include the hard carbon material, a binder and carbon black;
[0025] Preferably, the binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and polystyrene rubber;
[0026] Preferably, the carbon black includes one or more of Ketjen black and Super P;
[0027] Preferably, the mass ratio of the hard carbon material, the binder and the carbon black is (2-10): (2-10): 100, preferably 10: 10: 100;
[0028] Preferably, the current collector material of the negative electrode of the lithium ion battery is selected from any one of pure copper foil, carbon-coated copper foil, pure aluminum foil, carbon-coated aluminum foil and stainless steel foil.
[0029] The present application also provides a lithium ion battery, comprising the lithium ion battery negative electrode;
[0030] Preferably, the method for preparing the lithium-ion battery comprises:
[0031] The hard carbon material, the binder and the carbon black are mixed to obtain a slurry, which is then coated on a current collector and dried to obtain a negative electrode of a lithium-ion battery, and then assembled under an argon atmosphere using a lithium-ion ether electrolyte to obtain a lithium-ion battery;
[0032] Preferably, in the argon atmosphere, the oxygen content is less than 1 ppm and the water content is less than 1 ppm;
[0033] Preferably, the lithium salt in the lithium battery ether electrolyte includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide;
[0034] Preferably, the concentration of the lithium salt in the lithium battery ether electrolyte is 0.5-2 mol / L.
[0035] The present application also provides an electrical device, including the lithium-ion battery.
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] The hard carbon material provided by the present application innovatively uses taro as a raw material and has low cost.
[0038] The present application provides a method for preparing a hard carbon material for a negative electrode of a lithium-ion battery, which is obtained by freeze-drying and high-temperature treatment under an inert atmosphere. The hard carbon material has a rich porous structure, so that lithium metal can be firmly attached to the surface and pores of the hard carbon material. In addition, the rich pore structure of the hard carbon material provides a fast channel for the movement of lithium ions while limiting the unlimited growth of lithium dendrites. Compared with the battery negative electrode made of traditional amorphous carbon, it has a stronger lithium ion loading capacity, thereby enhancing the large current discharge capacity of the lithium-ion battery during the discharge process.
[0039] The negative electrode hard carbon material prepared by the preparation method provided in the present application has stable properties, achieves efficient and stable circulation in lithium-ion batteries, and exhibits excellent rate performance; the hard carbon material has high specific capacity, high stability and has prospects for large-scale development.
[0040] The lithium-ion battery negative electrode, lithium-ion battery and electrical equipment provided in this application have excellent electrical properties. (IV) Description of the drawings
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0042] Figure 1 is a process flow chart for manufacturing the hard carbon material;
[0043] Figure 2 1A / g of the hard carbon material in Examples 1, 2, and 3 -1 Cyclic curves and Coulomb efficiency diagrams;
[0044] Figure 3 is the XRD pattern of the hard carbon material prepared in Examples 1, 2 and 3;
[0045] Figure 4 , Figure 5 These are SEM images of the hard carbon material prepared in Example 1 at different magnifications. (V) Specific implementation methods
[0046] The present invention will be further described below in conjunction with specific embodiments.
[0047] Example 1
[0048] Step 1: Add 100g peeled taro and 50g water and mash into fine taro paste;
[0049] Step 2: After freezing in a refrigerator for 2 hours to set, transfer to a freeze dryer, freeze-dry the mixture at a cold trap temperature of -100°C and a vacuum degree of 15 Pa for 72 hours to obtain a pretreated biomass hard carbon material;
[0050] Step 3: calcining the material described in step 2 at 750° C. for 2 h under nitrogen atmosphere protection, with a heating rate of 15° C. / min;
[0051] Step 4: After calcination, take out the active material in the crucible and add 1 mol / L hydrochloric acid to wash until the salt impurities are washed away;
[0052] Step 5: Place the product obtained in step 4 in a constant temperature drying oven at 80°C and dry for 10 hours;
[0053] Step 6: ball-mill the active material obtained in step 5, and sieve to obtain a powder with a particle size of 400 mesh;
[0054] Figure 3 The XRD pattern of the hard carbon material synthesized by the above steps is: Figure 4 , Figure 5 This is a scanning electron microscope image of the hard carbon material synthesized by the steps described above.
[0055] Based on the synthesized hard carbon material, it is mixed with polyvinylidene fluoride and Ketjen black in a ratio of 8:1:1 and the obtained slurry is uniformly coated on the copper current collector by a doctor blade method or a spraying method, and the electrode is obtained after drying. The battery is assembled in an argon atmosphere, and the oxygen content and water content in the argon atmosphere are less than 1ppm. The electrolyte is a mixed solution of 1mol / L bistrifluoromethylsulfonyl imide lithium dissolved in ethylene glycol dimethyl ether / 1,3-dioxolane (mass ratio is 1:1) and 1% lithium nitrate.
[0056] In lithium-ion batteries, the obtained hard carbon materials have a high -1 At a high current density of 342 mAh g -1 After 100 cycles, the specific capacity is 254 mAh g -1 .
[0057] Example 2
[0058] The hard carbon preparation and lithium ion button battery assembly process of this embodiment are the same as those of Embodiment 1, with the only difference being that the high-temperature carbonization heating temperature used in this embodiment is changed to 500°C.
[0059] Example 3
[0060] The hard carbon preparation and lithium ion button battery assembly process of this embodiment are the same as those of Embodiment 1, with the only difference being that the high temperature carbonization heating temperature used in this embodiment is changed to 1000°C.
[0061] The constant current charge and discharge performance tests of the three assembled lithium-ion half-cells are carried out. The test results are as follows: Figure 2 As shown, the test voltage is 0.01-3V. Figure 2 It can be seen that the hard carbon material prepared by changing the high-temperature carbonization heating temperature to 750 °C has a -1 Under high current density, the specific capacity is higher than that of materials at 500℃ and 1000℃ after 100 cycles, so 750℃ is the optimal temperature.
[0062] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a lithium ion battery negative electrode hard carbon material, the preparation method being characterized in that: The following steps are involved: Step 1: Steam the taro skin and add appropriate amount of water to make fine taro paste; Step 2: After freezing in a refrigerator for 2 hours to set the shape, transfer to a freeze dryer for freeze drying to obtain a pretreated biomass hard carbon material; Step 3: subjecting the material described in step 2 to high temperature treatment in a protective atmosphere; Step 4: After the high temperature treatment, the active material is taken out and pickled to remove salt impurities; Step 5: Place the product obtained in step 4 in a drying oven for drying; Step 6: The active material obtained in step 5 is ball-milled and sieved to obtain a powder with a particle size of 400 mesh.
2. The preparation method according to claim 1, characterized in that: The temperature range of the cold trap for freeze drying is -20-200°C, the vacuum range is 10-20 Pa, and the time range is 24-96 hours. Preferably, the cold trap temperature of the freeze-drying treatment is -100°C, the vacuum degree is 15 Pa, and the time is 72 hours.
3. The preparation method according to claim 1, characterized in that: The high temperature treatment temperature range is 500-1500°C, and the heating rate range is 5-20°C / min; Preferably, the high temperature treatment temperature is 500°C, 750°C, or 1000°C, and the heating rate is 15°C / min.
4. The preparation method according to claim 1, characterized in that: The gas in the protective atmosphere includes one or more of nitrogen, argon, carbon dioxide, and hydrogen, and the gas flow rate ranges from 50 to 200 mL / min; Preferably, the protective atmosphere is nitrogen, and the gas flow rate is 80 mL / min.
5. The preparation method according to claim 1, characterized in that: The acid solution used for pickling includes at least one of hydrochloric acid, sulfuric acid, nitric acid and acetic acid, and the concentration range of the acid solution is 0.5-3 mol / L; Preferably, the acid solution used in the pickling is hydrochloric acid with a concentration of 1 mol / L.
6. The preparation method according to claim 1, characterized in that: The drying temperature range is 60-100°C and the time range is 5-24h; Preferably, the drying temperature is 80° C. and the drying time is 10 h.
7. The preparation method according to claim 1, characterized in that: The ball milling time range is 3-24h; Preferably, the ball milling time is 12 h.
8. A hard carbon material, characterized in that: The hard carbon material is prepared using the method for preparing the hard carbon material according to any one of claims 1 to 7.
9. A negative electrode for a lithium ion battery, characterized in that: The raw materials include the hard carbon material according to claim 8, a binder and carbon black; Preferably, the binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and polystyrene rubber; Preferably, the carbon black includes one or more of Ketjen black and Super P; Preferably, the mass ratio of the hard carbon material, the binder and the carbon black is (2-10): (2-10): 100, preferably 10: 10: 100; Preferably, the current collector material of the negative electrode of the lithium ion battery is selected from any one of pure copper foil, carbon-coated copper foil, pure aluminum foil, carbon-coated aluminum foil and stainless steel foil.
10. A lithium ion battery, characterized in that: A lithium-ion battery negative electrode comprising the negative electrode of claim 9; Preferably, the method for preparing the lithium-ion battery comprises: The hard carbon material, the binder and the carbon black are mixed to obtain a slurry, which is then coated on a current collector and dried to obtain a negative electrode of a lithium-ion battery, and then assembled under an argon atmosphere using a lithium-ion ether electrolyte to obtain a lithium-ion battery; Preferably, in the argon atmosphere, the oxygen content is less than 1 ppm and the water content is less than 1 ppm; Preferably, the lithium salt in the lithium battery ether electrolyte includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; Preferably, the concentration range of the lithium salt in the lithium battery ether electrolyte is 0.5-2 mol / L.
11. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 10.
Citation Information
Cited By
Lithium ion battery electrode and preparation method and application thereof
CN121011638A